Perancangan Concave Plate Collector Sebagai Sistem Penyerap Solar Energy - Jefri Ramadan; Awaludin Martin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Energy demand throughout the world is increasing gradually as a result of advances in science and technology. The fossil energy that have been used to met these needs have been decreasing and one day it will definitely run out. The increasing use of fossil fuels results in the production of CO2 emissions which always increase every year. Solar energy is energy that comes from sunlight, but the heat produced by this sunlight tends to be low, so to take advantage of this solar energy, technology is needed that can convert the heat temperature from that source, namely the solar collector. One of them is the concave plate collector, which will be used as a solar energy absorber system to be applied to the organic rankine cycle (ORC). The highest temperature reached for heating water is 56.6ºC, able to provide energy contribution of 43.4% of the total energy required with an organic rankine cycle efficiency of 4.489%.Keywords: concave plate collector, organic rankine cycle.